2019
DOI: 10.1590/1982-4327e2933
|View full text |Cite
|
Sign up to set email alerts
|

Child Distributive Behavior and Inhibitory Control in a Private Context

Abstract: Several studies have sought to assess the cognitive aspects underlying the sharing of goods. This work aimed to evaluate whether there is a relationship between inhibitory control and distributive behavior in a private context (total anonymity of the distributor). One hundred and thirty-six children aged between three and 12 years participated in a dictatorial game and a standard Stroop task. Age, inhibitory control and distributive behavior were positively correlated, but only age was predictive of sharing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…There was no association between effortful control and moral behavior. Cowell et al (2015), Reis and Sampaio (2019), Tan et al (2020), and Wildeboer et al (2017) reported that executive functions were not a significant predictor for moral behavior like, sharing, helping, donating or telling the truth. However, Cowell et al (2017) reported that executive functions were a significant predictor for sharing.…”
Section: Inhibitory Controlmentioning
confidence: 90%
See 4 more Smart Citations
“…There was no association between effortful control and moral behavior. Cowell et al (2015), Reis and Sampaio (2019), Tan et al (2020), and Wildeboer et al (2017) reported that executive functions were not a significant predictor for moral behavior like, sharing, helping, donating or telling the truth. However, Cowell et al (2017) reported that executive functions were a significant predictor for sharing.…”
Section: Inhibitory Controlmentioning
confidence: 90%
“…Executive functions comprise cross-domain, social and cognitive abilities and processes that encompass behavioral, emotional and cognitive functions and control, including future-oriented, planned, and regulated behavior (Baker et al, 2021;Cowell et al, 2015Cowell et al, , 2017Zelazo & Müller, 2011). Effortful control and inhibitory control are also considered to be components of executive functions (Diamond, 2013;Reis & Sampaio, 2019;Smetana et al, 2012). Furthermore, shift in attention or flexibility, planning skills and working memory are defined as aspects of executive functions (Cowell et al, 2015;Hinnant et al, 2013).…”
Section: Executive Functionsmentioning
confidence: 99%
See 3 more Smart Citations